SIKMA : Pengembangan Aplikasi Sistem Informasi Konter Makan Berbasis Website di PT. Pindad Kiaracondong Bandung - Hibatulloh, Iqbaal; Fadila, Nadia Zahra Nisa; Mandasari, Rizza Indah Mega (eProceedings of Applied Science, 2025)
Abstract—The Sistem Informasi Konter Makan (SIKMA) or Cafeteria Counter Information System is a web-based application designed to support the process of submission, management, and distribution of employee cafeteria counter services at PT Pindad Kiaracondong, Bandung. The cafeteria counter is part of the company’s cafeteria services that regularly provides meals for employees. As a state-owned manufacturing company with thousands of employees, PT Pindad has complex needs in managing meal services efficiently and in a wellstructured manner. The previous manual process, from recording submissions to reporting realization, often caused issues such as delays, data errors, and coordination difficulties between departments.This application was developed using the Laravel framework with the Model-View-Controller (MVC) approach, MySQL database, and a Tailwind CSS-based interface. SIKMA is equipped with role-based login features (employee, division admin, Human Capital and People Organization (HCPO), and Yayasan Cakra Binangkit (YCB)), personnel data management, meal service submission, validation by HCPO admin, distribution management by YCB, and a meal rating system by employees. The system also supports barcode scanning for meal retrieval and provides interactive graphical visualization of cafeteria counter service realization data.The development process consisted of literature study, requirement analysis through interviews with PT Pindad users, interface design using Figma, code implementation in an integrated project, and application testing using the black box method and Likert scale questionnaires. The test results show that the application functions as expected, is easy to use, and can improve efficiency and accuracy in meal service management. With the implementation of SIKMA, the company not only enhances employee productivity but also strengthens data integration and transparency in its internal service system. Keywords—Information System, Web Application, Cafeteria Counter, Barcode, Laravel, PT Pindad, SIKMA